„Mówię rzecz, jak jest – kolor biały nie rozwija się przez niuanse”. Wybrane przykłady funkcjonowania symboliki bieli w liryce Cypriana Norwida - Wójcik, Maria (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article presents functioning of whiteness as a symbol in Cyprian Norwid’s poetic works, based on selected examples. The author indicates that this issue has not yet been fully investigated and the article is only an outline of the subject due to its extent. The research is focused on several selected meanings: whiteness of the landscape, white color as a symbol of nobility and divinity, of virginity and purity, even of ethical ambiguity. Author also distinguishes between themes of whiteness and pallor. White color can be mainly associated with theme of the light in poetry, which Norwid very often used, but this not makes the only meaning. Ancient and Christian culture defined the semantics of white color as a symbol of purity, virginity and divinity and such meanings dominate in Norwid’s poems. Interestingly, the writer also used the whiteness to describe the nature of evil. The poet juxtaposed the symbolism of white by comparing it to dirt or black color, he accumulated themes related to whiteness as well to show its meaning in a broader context. In conclusion, Norwid, in his poetic works, often used the symbolism of whiteness in the sense determined by culture, however, he did it in an original way, enriching it with his own ideas and associations.
“I Say as It Is – White Color Does Not Develop Through Nuances”. Selected Examples of the Functioning of Whiteness Symbol in Cyprian Norwid’s Poems
Niniejszy artykuł stanowi gruntownie przepracowany i rozbudowany fragment mojej pracy magisterskiej pt. „Symbolika czerni i bieli w twórczości Cypriana Kamila Norwida” (Rzeszów 2017), którą napisałam pod kierunkiem dra hab. prof. UR Marka Nalepy. W tytule publikacji wykorzystałam sformułowanie Norwida zaczerpnięte z jego listów: C. Norwid, „Pisma wszystkie”, zebrał, tekst ustalił, wstępem i uwagami krytycznymi opatrzył J. W. Gomulicki, t. VIII: Listy, Warszawa 1971, s. 256.
Keywords: symbolism of whiteness; romanticism poetry; Cyprian Norwid; 19th-century Polish poetry; symbolika bieli; poezja romantyzmu; poezja polska XIX wieku